Resurrection of Leucobryum scalare Müll.Hal. ex M.Fleisch. (Bryophyta, Leucobryaceae) based on phylogenetic and morphometric evidence - Tiwutanon P. (2023)
Leucobryum scalare was described in 1904 but its taxonomic status has been disputed, being reduced to a variety of Leucobryum aduncum or synonymized with Leucobryum aduncum. The taxonomic confusion of this taxon has remained unresolved. Hence, we revisited the taxonomic status of the taxon using phylogenetic and morphometric approaches. A total of 27 samples from Leucobryum aduncum var. aduncum and Leucobryum aduncum var. scalare were used to generate data from four markers, including ITS1, ITS2, atpB-rbcL spacer, and trnL-trnF. The concatenated dataset was used to reconstruct a phylogenetic tree. Both qualitative and quantitative morphological characters were measured and analyzed with Principal Component Analysis (PCA) and PERMANOVA. The results showed that the two taxa are closely related but they are reciprocally monophyletic. Both qualitative and quantitative characters could also separate Leucobryum aduncum var. scalare from Leucobryum aduncum var. aduncum as shown with PCA and PERMANOVA. We propose the resurrection of the species rank for Leucobryum scalare as separate from Leucobryum aduncum. This work highlights the need for a more thorough revision of Leucobryum to clarify the actual level of diversity in this genus.